2013
DOI: 10.1186/1477-7525-11-168
|View full text |Cite
|
Sign up to set email alerts
|

The Swedish version of the multidimensional scale of perceived social support (MSPSS) - a psychometric evaluation study in women with hirsutism and nursing students

Abstract: BackgroundThe Multidimensional Scale of Perceived Social Support (MSPSS) is a short instrument, developed to assess perceived social support. The original English version has been widely used. The original scale has demonstrated satisfactory psychometric properties in different settings, but no validated Swedish version has been available. The aim was therefore to translate, adapt and psychometrically evaluate the Multidimensional Scale of Perceived Social Support for use in a Swedish context.MethodIn total 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
79
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(106 citation statements)
references
References 42 publications
10
79
0
11
Order By: Relevance
“…Further evidence of convergent and discriminant validity was observed through the MSPSS's significant negative association with a measure of loneliness (UCLA LS) and non‐association with verbal ability (EVT‐2). Findings in this study are similar to those reported by Ekbäck et al (2013), which also supported the three‐factor structure.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Further evidence of convergent and discriminant validity was observed through the MSPSS's significant negative association with a measure of loneliness (UCLA LS) and non‐association with verbal ability (EVT‐2). Findings in this study are similar to those reported by Ekbäck et al (2013), which also supported the three‐factor structure.…”
Section: Discussionsupporting
confidence: 92%
“…The MSPSS is preferred for use in many contexts because it is brief, and provides measures of support from significant others (SO), family (FAM), and friends (FRI). Studies in non‐incarcerated populations suggest that the MSPSS has good convergent and discriminant validity and internal consistency reliability in many populations (Canty‐Mitchell & Zimet, 2000; Ekbäck, Benzein, Lindberg, & Årestedt, 2013; Zimet et al, 1988; Zimet et al, 1990). There is also empirical support for the original three‐factor structure of the MSPSS (i.e., one factor for SO, FAM, and FRI) in most populations, including university students (Dahlem et al, 1991; Zimet et al, 1988), urban African American adolescents (Canty‐Mitchell & Zimet, 2000), South African youth (Bruwer et al, 2008), and patients affected by psychiatric disorders (Cecil, Stanley, Carrion, & Swann, 1995; Vaingankar et al, 2012).…”
Section: The Multidimensional Scale Of Perceived Social Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…The MSPSS is a short instrument (12 items), developed to assess perceived social support (7). The validity and reliability of the Turkish version were established by Eker et al (9).…”
Section: Abdurrahman Yurtaslan Ankara Oncology Training and Research mentioning
confidence: 99%
“…The sample size in the study should be 10–15 subjects per item for factor analysis of scale [23]. The sample size of our research was enough for factor analysis of BARSHSS-CV.…”
Section: Discussionmentioning
confidence: 99%